If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = 3400 + 0.6Y Solving Y = 3400 + 0.6Y Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-0.6Y' to each side of the equation. Y + -0.6Y = 3400 + 0.6Y + -0.6Y Combine like terms: Y + -0.6Y = 0.4Y 0.4Y = 3400 + 0.6Y + -0.6Y Combine like terms: 0.6Y + -0.6Y = 0.0 0.4Y = 3400 + 0.0 0.4Y = 3400 Divide each side by '0.4'. Y = 8500 Simplifying Y = 8500
| 107=6x+17 | | (2y-3)(y+1)=-4(2y-3) | | x^3-3x^2-3x-4=y | | k(3k+2)=k(5k+-4) | | 30!/27!3!= | | 8x+13y=120 | | Y=2775+0.75Y | | K(3k+2)=k(5k-4) | | (3x+7)(2-x)=0 | | 13x+21=6x+196 | | 7x-3y-(5x-2y)= | | 5x^3+2x+1.33=0 | | 17-4x=5-7x | | 0.6x-5=7 | | 0.8x+30=14 | | 5x^3+2x-1.33=0 | | -10x^3-3(10)+1=0 | | 6x+5y-2w+2x-8y-9w= | | 2x+5x^3=1.33 | | 2(x+8)=8 | | n^3+n^2-21n-45=0 | | 2ab-3ab+ab= | | 1.6z-0.6z-0.7=-6.8 | | x+3=2(x+3) | | z-6.6=3.2 | | -1+3x=-3+25 | | 4.1n-3.1n-2.9=0.4-4.3 | | 2x+9=-81-x | | 13=v-11 | | 4(2x+1)+(9x+6)=44 | | (x^2)-x-9=0 | | (1-3x)/4=(x-2)/2 |